Do political parties matter in defining political careers in Brazil? - Vitor Eduardo Veras de Sandes Freitas; Diarlison Lucas Silva da Costa (Política & Sociedade, 2019)
This article aims to analyze whether political parties are important on the political career choices of Brazilian federal deputies. Therefore, this work is based on the theoretical contributions on political career that have shown that the main career pattern presented by congressmen is static, that is, seek for re-election (PEREIRA; RENNÓ, 2013). The explanation pointed out is that this choice is the safest, regardless of the parties to which they are affiliated. However, other authors have called attention to the need to verify the importance of factors that differentiate deputies in a more disaggregated analysis of political careers such as participation in the government coalition or opposition groups (BORGES; SANCHES FILHO, 2016), as well as the differences presented within the districts (COSTA, 2018; CORRÊA, 2016). In addition, the party variable can be an important factor in defining the careers due to ideological differences between the parties (MARENCO; SERNA, 2007) and the strategic interests of the parties in the elections for Mayor in the big cities. Thus, this article aims to test if the party variable matters for the career choice of federal deputies, as well as the other variables portrayed in the literature. The results show that deputies of leftist parties and the government coalition are more likely to run for reelection and the city hall than those of the right and center.